An attack proof intelligent digital watermarking based on safe region of fast fourier transform - Olanrewaju, Rashidah Funke; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Aburas, A. A. (2010)
Recent advancement in digital medium has created a need for secure transfer and transaction over the internet. The fact is that the current digital distribution and storage technologies are great threat to multimedia industries where unlimited number of perfect copies can be produce illegally. In this paper we discuss digital watermarking as a means of hiding owner’s copyright message in images. At the moment, the most critical issue faced by the watermarking system is determining the best place to hide watermark data. We propose a method, an attack proof intelligent system, in which Artificial Neural network is use to locate the Safe Region in the host image and the watermark is embedded based on the located Safe Region in Fast Fourier Transform domain. Experiment on a large set of natural images shows the robustness of the new scheme. The implementation results have shown that this watermarking algorithm has high level of imperceptibility and the watermark bit were all recovered correctly. Keywords: (Artificial Neural Network, Back Propagation algorithm, Fast Fourier Transform, FFT, Image watermarking, Safe Region,)